2002
DOI: 10.1046/j.1365-2834.2002.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical supervision using video-conferencing technology: a reflective account

Abstract: This paper discusses three nursing practitioners' experiences of clinical supervision using video-conferencing (VC) technology. The study, based on supportive action research, involved 40 practising community and hospital nurses from a variety of specialties and took place over an 18-month period. The research was collaborative, educational and applied and focused on the effects of remote clinical supervision on the development of professional practice. Data were obtained through pre- and post-study questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 18 publications
0
27
1
5
Order By: Relevance
“…This is not consistent with the results obtained by Marrow et al (2002), who reported that distance supervision strategies are widely used in PHC. We believe that this result may be explained by the fact that the sampled PHC nurses work in institutions located in costal, non-isolated urban areas and have extensive nursing teams.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is not consistent with the results obtained by Marrow et al (2002), who reported that distance supervision strategies are widely used in PHC. We believe that this result may be explained by the fact that the sampled PHC nurses work in institutions located in costal, non-isolated urban areas and have extensive nursing teams.…”
Section: Discussioncontrasting
confidence: 99%
“…Supervision by videoconference, namely using Skype ® software, allows supervisors and supervisees to communicate orally and establish visual contact. Nurses prefer to use this strategy rather than using the telephone or email (Marrow, Hollyoake, Hamer, & Kenrick, 2002). Primary health care nurses use distance supervision strategies more often than hospital nurses because of the difficulties in accessing the clinical supervisor in a timely and appropriate manner as a result of working in separate and often distant facilities (Marrow et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…According to this systematic review [26], group clinical supervision would be particularly effective, especially if conducted off-site, held frequently and of substantial length. Also, the rural nurses felt that their clinical supervision experiences were valuable in improving their understanding about their practice, as well as increasing their self-awareness and ability to critically reflect [31]. …”
Section: Resultsmentioning
confidence: 99%
“…Robson & Whelan (2006) concluded that the use of the telephone is more significant for the supervisee working in more isolated areas or locations distant from the main working place. Marrow et al, (2002) found that the distance supervision strategies are not often adopted in hospital settings but widely implemented in primary health care units and that nurses working in rural areas prefer the ICT enabling visual communication.…”
Section: Responsibility Of the Organizing Committee Of The Conferencementioning
confidence: 99%